THE REALIZATION OF SPEECH ACT TYPES IN TERMINATING CONTRACTS - Fadisa, Debby Oktavia (2016)
This paper entitled "The Realization of Speech Act Types in Terminating Contracts" aims to investigate the speech act types in terminating contracts based on Searle's theory and to discover the influences of three sociological variables such as power, social distance, and rank of imposition toward the speech act types. The study uses descriptive-qualitative method to analyze the data. The main data are collected through the DCT questionnaires from 15 male and 15 female participants in English Literature Program in English Education Department of Indonesia University of Education. The study revealed that in terminating contracts, there are only four types of speech act realized such as Representatives, Directives, Commissives, and Expressives. In the present study, female participants use Directives mostly in terminating contract, while Representatives is the most frequent used by male participants. The influences of sociological variables show that the participants use Representatives, Directives, and Commissives in order to be polite and to avoid threatening the face of the hearer. Meanwhile, the use of Expressives in order to respect the hearer is not influenced by the sociological variables. Keywords: Pragmatics, Speech Act Types, Face-threatening Acts, Politeness